Was the Asian crisis a wake-up call? foreign reserves as self-protection - Mendoza, Ronald U. (ProQuest LLC, 2008)
This paper digs deeper into the self-protection rationale for holding reserves by examining the empirical link between reserve holding patterns and crisis vulnerability. Analyzing data for 51 developing countries during the period 1982-2004, it finds evidence that the elasticity of developing country reserves with respect to certain crisis vulnerability indicators like foreign debt service and total external liabilities seems to be higher in the post-Asian crisis period, suggesting that policymakers' precautionary responsiveness by holding more reserves has increased. Grouping countries according to their type of vulnerability (commodity, debt or sudden stop related), countries prone to sudden stops in capital inflows also seem to have adjusted their policies the most towards higher precautionary reserve holding. However, contrary to common assertion, China's reserve holding patterns seem to be in line with what developing countries more generally seem to be undertaking.--Abstract.